OPTIMALISASI BANYUWANGI IN YOUR HAND MELALUI FITUR PENGINTEGRASIAN GPS DAN TAX REFUND GUNA MENINGKATKAN CUSTOMER SATISFACTION - Utama, A.A Gde Satia; Rahayu, Puput Puji; Harianto, Shandy; Daniel, Debby Ratna (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2019)
Banyuwangi In Your Hand is an application connected with fiber optic that has been connecting 280 kilometers in 28 districts in Banyuwangi Regency. However, the increasing numbers of the tourist is not in line with the numbers of application download. Therefore, the application needs to be evaluated in terms of the feature and program. This study examines the process of information update related to the location of tourism objects in Banyuwangi. This is a qualitative descriptive study. Data were collected from literature study and interviews with the tourists visiting Banyuwangi. This study proposed the idea of integrating GPS in Banyuwangi In Your Hand application to increase the performance of information update about tourism spots in Banyuwangi. This study also proposed to add tax refund application on the transaction feature in order to increase the value of the Banyuwangi In Your Hand application. The aim of the addition of both systems in Banyuwangi In Your Hand application was to increase customer satisfaction Keywords: Banyuwangi In Your Hand, GPS, tax refund, customer satisfaction